Obesity and overweight as CAE comorbidities and differential drug response modifiers. (26th April 2016) - Arya, Ravindra; Gillespie, Catherine W.; Cnaan, Avital; Devarajan, Mahima; Clark, Peggy; Shinnar, Shlomo; Vinks, Alexander A.; Mizuno, Kana; Glauser, Tracy A.
Abstract : Objective: This study examined whether overweight and obesity are pretreatment comorbidities and predictors of short-term drug response in newly diagnosed untreated childhood absence epilepsy (CAE). We also examined whether dietary intake accounts for observed pretreatment body mass index (BMI) distribution. Methods: Pretreatment height and weight were available for 445 of 446 participants in the NIH-funded CAE comparative effectiveness trial (NCT00088452). Twenty-four-hour dietary recalls were collected. Calculated BMI and dietary intake were standardized for age, sex, and race/ethnicity and compared to age-matched US population from the National Health and Nutrition Examination Survey (NHANES). Logistic regression models tested BMI as a predictor of treatment response. Pharmacokinetic variables were explored as contributors to differential drug response. Results: After standardizing for demographic differences, children with CAE were more likely to be overweight (19.3% vs 13.8%; p < 0.001) or obese (14.5% vs 11.5%; p < 0.001) than NHANES controls. The combined prevalence of overweight and obesity was 33.8% in the CAE cohort and 25.3% among controls ( p < 0.001). Mean daily energy intake (difference −79.5 kcal/day, p = 0.04) and daily carbohydrate intake (difference −10.7 g/day, p = 0.04) were lower in the CAE group than in NHANES controls. With increasing baseline BMI z score, the efficacy and effectiveness of ethosuximide and valproic acid over lamotrigine became more pronounced, despite no significant differences in drug exposure and trough levels. Conclusions: Overweight and obesity are more prevalent in children with newly diagnosed CAE than in age-matched peers, despite lower caloric and carbohydrate intake. Baseline BMI may also predict differential drug response, which cannot be attributed to pharmacokinetic differences.